Effect of passive transfer status on response to a glycoprotein E (gE)-negative bovine herpesvirus type 1 (BoHV-1) and bovine respiratory syncytial virus (BRSV) vaccine and weaning stress in pre-weaned dairy calves. Issue 1 (1st January 2018) - Dunn, Amanda; Welsh, Michael; Gordon, Alan; Arguello, Anastasio; Morrison, Steven J.; Earley, Bernadette
ABSTRACT: The study objectives were to: 1) examine how calves of divergent immune status respond to BRSV vaccination at 3 weeks of age; 2) trace glycoprotein E negative BoHV-1 antibodies from vaccinated dams to calf sera and to investigate how passive transfer affects response to live BoHV-1 vaccine at 6 weeks of age; 3) explore the impact of passive transfer status on blood metabolites around weaning. Thirty seven Holstein cows and their calves were included in the study. All cows were immunised with a commercial marker vaccine against BoHV-1(gE-) administered intra-muscularly at 4 month prior to the start of calving. Calves were assigned to 1 of 2 colostrum treatment groups: 1) 5% of BW in colostrum fed at birth, or 2) 10% of BW in colostrum fed at birth. Calves were also immunised at 3 weeks of age with a respiratory commercial vaccine, and a booster administered 4 weeks later. Calves were also immunised against BoHV-1 at 6 weeks of age, using one dose of a live commercial vaccine. The results demonstrated that level of passive immunity had no effect on immune response to vaccination and the importance of feeding colostrum from vaccinated BoHV-1 gE- dams to provide calves with passive protection against IBRV.